Cohomological characterization of universal bundles of G(1,n) - Arrondo, Enrique; Tocino-Sánchez, Alicia (Elsevier, 2019)
We characterize directs sums of twists of symmetric powers of the universal quotient bundle over the Grassmannian of lines. We use a method that could be used for analogue results on any arbitrary variety, and that should give stronger results than using the standard technique of Beilinson's spectral sequence.
Keywords: Schur, Funciones de; Matemáticas; Grassmannian; Cohomology; Universal bundles; Serre duality; Eagon-Northcott complexes; Schur functor